Steady-state performance analysis of serial transfer lines subject to machine and buffer failure - Lipset, R.; Van Til, R.P.; Sengupta, S. (IEEE transactions on automatic control, 1999)
In modern automated production lines, it is common to connect adjacent machines with buffers. Since these buffers are mechanical devices, they are prone to failure. Previous research concerning the steady-state analytical modeling of serial transfer lines assumed that buffers are completely reliable. The paper considers the unreliable buffer and presents a model of the serial transfer line incorporating this concept. A decomposition technique is developed for the general serial transfer line with unreliable buffers, and an algorithm for computing the solution of the model is presented.